Developing Profoundabilities: A New Model for Adult Educators - Carol Rogers Shaw; Michael Kroth; Davin Carr-Chellman (Adult Education Research Conference, 2022)
The Profoundabilities Model of human potentiality highlights the development of remarkable abilities in all learners. It emphasizes well-being and flourishing through a strength-based approach to adult education.
Keywords: profoundabilities; disability; strengths-based; flourishing